2020
DOI: 10.2320/matertrans.m-m2020806
|View full text |Cite
|
Sign up to set email alerts
|

Electrorefining Behavior of Copper Shot-Shaped Anode Containing High Levels of Platinum

Abstract: Increased amounts of secondary copper resources with higher levels of impurities are being fed to copper smelters. To avoid passivation problems, low-grade copper that is derived from secondary resources is dissolved in sulfuric-acid solution, and the dissolved copper is recovered by electrowinning. Electrowinning is disadvantageous because of its higher power consumption compared with electrorefining. Based on an electroplating technique that uses basket electrolysis with a ball-shaped anode and another exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Iizuka et al reported that basket electrolysis with CuPt alloy anodes with a Pt content of 1 mass%, which are easily passivated during electrolysis, gave a dissolution ratio that was significantly higher for small shot anodes than for plate anodes. 23) In the basket electrolysis process, the characteristics of the anode film formed on the surface during electrolysis are especially important. In electrolysis with plate anodes, the effect of the anode film on passivation is mainly related to elution of Cu ions into the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Iizuka et al reported that basket electrolysis with CuPt alloy anodes with a Pt content of 1 mass%, which are easily passivated during electrolysis, gave a dissolution ratio that was significantly higher for small shot anodes than for plate anodes. 23) In the basket electrolysis process, the characteristics of the anode film formed on the surface during electrolysis are especially important. In electrolysis with plate anodes, the effect of the anode film on passivation is mainly related to elution of Cu ions into the electrolyte.…”
Section: Introductionmentioning
confidence: 99%